1983
DOI: 10.1172/jci110987
|View full text |Cite
|
Sign up to set email alerts
|

Functional improvement of jeopardized myocardium following intracoronary streptokinase infusion in acute myocardial infarction.

Abstract: A B S T R A C T The effect of reperfusion on regional left ventricular performance following acute myocardial infarction in man was determined. Intracoronary streptokinase was administered in 24 patients within 6 h of the onset of symptomns. 15 patients (62%) were successfully recanalized during the initial study. Mean percent radial shortening (%RS) in both the jeopardized and compensatory regions were determined using 23 radii from the centroid of diastolic and systolic angiographic silhouettes. Sequential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

1985
1985
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(26 citation statements)
references
References 19 publications
(40 reference statements)
0
23
0
3
Order By: Relevance
“…Improvement in ventricular function occurred gradually over the course of a few weeks. [81][82][83][84] One report 85 suggested that stunned myocardium could be recruited after thrombolytic therapy with small boluses of inotropes. These studies suggest that the ultimate return of cardiac function cannot be determined immediately after reperfusion.…”
Section: Myocardial Stunning In Humansmentioning
confidence: 99%
“…Improvement in ventricular function occurred gradually over the course of a few weeks. [81][82][83][84] One report 85 suggested that stunned myocardium could be recruited after thrombolytic therapy with small boluses of inotropes. These studies suggest that the ultimate return of cardiac function cannot be determined immediately after reperfusion.…”
Section: Myocardial Stunning In Humansmentioning
confidence: 99%
“…Some studies using epicardial strain gauges did not find an apparent hyperfunction of nonischemic areas (Banka and Helfant, 1974;Vokonas et al, 1976;Wyatt et al, 1976), indicating that the effects may not always be reflected transmurally. An increase in systolic motion in nonischemic areas has been noted in patients by echocardiography (Corya et al, 1975;Nieminen and Heikkila, 1976) and angiography (Rigaud et al, 1979;Stack et al, 1983;Sheehan et al, 1983).…”
mentioning
confidence: 98%
“…14. [21][22][23][24][25][26][27][28][29] This difference could not be explained by skewing of the known pretreatment clinical or laboratory risk factors, such as the delay before treatment or unusual resistance to SK, and could be ASuccessful treatment in 12 patients includes six who responded to initial infusions of low-(n = 2) or standard-dose SK (n = 4) plus six who responded to retreatment at standard dose after failure at low-dose SK.…”
Section: Discussionmentioning
confidence: 99%